2007
DOI: 10.1002/cncr.23168
|View full text |Cite
|
Sign up to set email alerts
|

Absolute lymphocyte count is a novel prognostic indicator in ALL and AML

Abstract: BACKGROUND.Leukemia is the leading cause of disease‐related death in children, despite significant improvement in survival and modern risk stratification. The prognostic significance of absolute lymphocyte counts (ALC) was evaluated in young patients with acute myeloblastic leukemia (AML) and acute lymphoblastic leukemia (ALL).METHODS.In all, 171 consecutive de novo cases of AML and ALL, age ≤21 years, were analyzed. Age, initial white blood cell count, cytogenetics, and bone marrow response were compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
69
3
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 42 publications
12
69
3
3
Order By: Relevance
“…The results obtained in the current study confirm the observations of other authors [3,5,6,11,13,17,19] that after ALL treatment children are in an immunocompromised state for up to 12 months. This concerns both cellular and humoral immunity.…”
Section: Discussionsupporting
confidence: 92%
“…The results obtained in the current study confirm the observations of other authors [3,5,6,11,13,17,19] that after ALL treatment children are in an immunocompromised state for up to 12 months. This concerns both cellular and humoral immunity.…”
Section: Discussionsupporting
confidence: 92%
“…30,36,37 Antecedent evidence verified that ALC and AMC were parameters to predict outcomes in several types of cancer. [14][15][16][17][18][19][20][38][39][40][41][42] ALC and AMC have been studied as combined factors in Hodgkin's lymphoma and diffuse large B-cell lymphoma. 19,[21][22][23][24][25][26] Results showed that ALC/AMC ratio and AMC/ALC prognostic scores seemed to be associated with outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that absolute lymphocyte count (ALC) [14][15][16][17][18][19] and peripheral blood absolute monocyte count (AMC) 19,20 at diagnosis can evaluate the prognosis in some lymphoid and hematological malignancies. Moreover, the value of the incorporation of ALC and AMC has been explored and several studies revealed that ALC/AMC ratio [21][22][23][24] and ALC/AMC prognostic score (low risk and normal ALC and AMC; intermediate risk, low ALC, or high AMC; high risk, low ALC, and high AMC) 19,25,26 were related to survival in certain types of lymphomas.…”
Section: Introductionmentioning
confidence: 99%
“…The third center administered post-HSCT i.t. therapy to all ALL patients and to high-risk AML patients where the AML patients generally considered to be high risk were AML FAB M4-M7 and AML FAB M0-M3 patients with a high presenting leukocyte count (WBC) (420 Â 10 9 /L) or another high-risk factor such as extramedullary involvement or slow response to primary treatment [8][9][10] (Table 1). The fourth center gave i.t.…”
Section: Patient Characteristicsmentioning
confidence: 99%